DEVELOPMENT OF INQUIRY-BASED DIGITAL WORKSHEET TO IMPROVE MATHEMATICAL THINKING ABILITY - Audina, Chamila Putri; Susanti, Ely; Aisyah, Nyimas (UNIVERSITAS MUHAMMADIYAH METRO, 2025)
One of the mathematical abilities that schools are expected to develop is students’ mathematical thinking ability. However, many students still struggle in this area due to the use of learning methods that are not aligned with students’ characteristics and learning environments. These methods often lack opportunities for student interaction and fail to accommodate individual learning levels, resulting in limited engagement and development of higher-order thinking. This condition indicates the need for innovative learning approaches that promote active involvement, interaction, and reasoning. Inquiry-based learning, supported by digital worksheets, is one such approach that can help improve students’ mathematical thinking. This research aims to develop valid and practical inquiry-based digital worksheets on the topic of cubes and beams for grade 8 students and to examine their potential to enhance students’ mathematical thinking ability. The study consists of two stages: the preliminary stage, which involves the development of the worksheet concept and design, and the prototyping stage, which includes self-evaluation, expert review, one-to-one, small group, and field testing. Validity data obtained from expert reviews show an average score of 87%, categorized as very valid, while practicality data yield an average score of 79%, categorized as practical. The students’ work on the tasks indicates a high level of mathematical thinking, with 79.3% of students categorized as very good, 10.3% as good, 3.4% as sufficient, and 6.9% as less. Interview results based on mathematical thinking indicators show that the most frequently demonstrated indicator is specialization, while conjecture appears the least. These findings suggest that inquiry-based digital worksheets have the potential to support the development of students’ mathematical thinking.Salah satu kemampuan matematis yang diharapkan dapat dikembangkan di sekolah adalah kemampuan berpikir matematis siswa. Namun, banyak siswa masih mengalami kesulitan dalam mengembangkan kemampuan ini akibat penggunaan metode pembelajaran yang tidak sesuai dengan karakteristik siswa dan lingkungan belajarnya. Metode tersebut sering kali tidak memberikan ruang interaksi antarsiswa dan tidak disesuaikan dengan tingkat kemampuan siswa, sehingga keterlibatan dan pengembangan kemampuan berpikir tingkat tinggi menjadi terbatas. Kondisi ini menunjukkan perlunya inovasi pembelajaran yang mendorong keterlibatan aktif, interaksi, serta penalaran siswa. Pembelajaran berbasis inkuiri yang didukung dengan lembar kerja digital merupakan salah satu pendekatan yang berpotensi meningkatkan kemampuan berpikir matematis siswa. Penelitian ini bertujuan untuk mengembangkan lembar kerja digital berbasis inkuiri pada materi kubus dan balok untuk siswa kelas VIII SMP yang valid dan praktis, serta mengetahui potensi pengaruhnya dalam meningkatkan kemampuan berpikir matematis siswa. Penelitian ini terdiri dari dua tahap, yaitu tahap pendahuluan yang menghasilkan konsep dan desain lembar kerja, serta tahap prototyping yang meliputi evaluasi diri, tinjauan ahli, uji perorangan, uji kelompok kecil, dan uji lapangan. Data validitas diperoleh dari hasil tinjauan ahli dengan skor rata-rata 87% (kategori sangat valid), sedangkan data kepraktisan memperoleh skor rata-rata 79% (kategori praktis). Hasil pengerjaan siswa menunjukkan kemampuan berpikir matematis yang tinggi, dengan 79,3% siswa berkategori sangat baik, 10,3% baik, 3,4% cukup, dan 6,9% kurang. Berdasarkan wawancara yang mengacu pada indikator berpikir matematis, indikator yang paling sering muncul adalah spesialisasi, sedangkan indikator yang paling jarang muncul adalah dugaan (conjecture). Temuan ini menunjukkan bahwa lembar kerja digital berbasis inkuiri berpotensi mendukung pengembangan kemampuan berpikir matematis siswa.